Peningkatan Keterampilan Menulis Teks Argumentasi dengan Metode Four Square pada Siswa Kelas XI - Dwisaptarida, Febrisa; Suhendra; Wiati, Iis (Universitas Muhammadiyah Surabaya, 2024)
Writing argumentative texts is essential to learning because students can express their opinions and views. This research aims to review the implementation of lesson study-based learning of argumentative text writing skills and the improvement of argumentative text writing skills using the four square method for class XI students. This research is included in Collaborative Classroom Action Research based on lesson study. The PTKK implementation was carried out in two cycles using data collection techniques in the form of tests and non-tests. The subjects in this research were 34 students in class XI A at SMAN 5 Bogor City. In this research, data was obtained on improving the writing skills of class XI students from cycle 1 to cycle 2. The average score obtained by students in cycle one reached 73.11, while in cycle two, they got an average score of 89,5. This data shows that the four square methods improve argumentative text writing skills of class XI A students at SMAN 5 Bogor City.